Islamic Economic Institutions’ Dynamics in Muslim and Non-Muslim Countries: Comparison of Morocco and Australia - Ash Shayiim, Muhammad; Luthfi Alifa, Naufal (Athallah Publishing Globalindo, 2025)
Studies on Islamic economic institutions have developed significantly as part of the discourse on alternative and inclusive economic systems. However, in practice, many obstacles remain in implementing Sharia principles amid digital transformation and global institutional dynamics. This research aims to comparatively analyze Islamic economic institutions in Morocco and Australia, focusing on institutional structures, regulations, and the socio-economic contexts that influence the performance and sustainability of these institutions. The research employs a quantitative method with a comparative approach between the two countries, using purposive sampling of Islamic economic institutions that have operated for at least five years and publish verified reports. Data were collected from secondary documentation and analyzed through descriptive statistics, mean difference tests, and variable correlation analysis. The findings indicate that the success of Islamic economic institutions is strongly influenced by national contexts and institutional systems. Morocco adopts a top-down institutional model integrated into state regulations, while Australia relies on community-driven innovation within a regulatory framework that remains unspecific. Therefore, Indonesia can strengthen its Islamic finance ecosystem by combining robust regulations with market-based innovations.